Pemahaman Masyarakat Desa Sigala-Gala terhadap Pinjaman Mekar dalam Kesejahteraan Perekonomian - Nurhakimah Akhirani; Raini Dalimunthe; Fierda Fierda; Arianto Hasibuan; Jamila Fahma Pulungan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the review of Islamic law on Mekar loans in Sigala-Gala Village. This type of research is qualitative. The subjects in this study are the people of Sigala-Gala Village who are Mekar customers as many as 10 people. Then the object of research is the review of Islamic law on mekar loans. The research data collection techniques used are observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawing. Then the data validity checking technique used is credibility, transferability, dependability and confirmability. The results found are that loans in Mekar are still classified as containing usury, because in practice loans in Mekar still take fines for late returns, this is not in accordance with the principles of justice, and help. Islam also prohibits the existence of unfairness in borrowing, based on this, loans at Mekar are not yet sharia principles.